2022
DOI: 10.1016/j.celrep.2022.110336
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 mRNA vaccine induces robust specific and cross-reactive IgG and unequal neutralizing antibodies in naive and previously infected people

Abstract: Understanding vaccine-mediated protection against SARS-CoV-2 is critical to overcoming the global COVID-19 pandemic. We investigate mRNA vaccine-induced antibody responses against the reference strain, seven variants, and seasonal coronaviruses in 168 healthy individuals at three-time points: before vaccination, after the first, and after the second doses. Following complete vaccination, both naïve and previously infected individuals developed comparably robust SARS-CoV-2 spike antibodies and variable levels o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 88 publications
5
43
1
Order By: Relevance
“…Collectively, Seronet institutions reported development of 27 in-house ELISA methods (Table 1). 6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The majority of ELISA methods were developed for testing of serum and/or plasma, with additional methods available for testing dried blood spots (DBS), saliva/oral fluid, and breast milk. Two methods have been granted FDA EUA approval, 3 methods are pending FDA EUA, 4 methods are validated for high-complexity testing in a CLIA-certified laboratory, and 18 methods are for research-use only (RUO).…”
Section: Seronet Serology Assay Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Collectively, Seronet institutions reported development of 27 in-house ELISA methods (Table 1). 6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The majority of ELISA methods were developed for testing of serum and/or plasma, with additional methods available for testing dried blood spots (DBS), saliva/oral fluid, and breast milk. Two methods have been granted FDA EUA approval, 3 methods are pending FDA EUA, 4 methods are validated for high-complexity testing in a CLIA-certified laboratory, and 18 methods are for research-use only (RUO).…”
Section: Seronet Serology Assay Datamentioning
confidence: 99%
“…Narowski et al also found a significant decline in the longitudinal sensitivity of their lab-developed nucleocapsid assay in a study of healthcare workers. 6 Perez-Saez et al similarly demonstrated that the rates of sero-reversion at least 8 months after the initial infection differed greatly depending on the serological assay used. 4 While the sero-reversion rate of the EuroImmun semiquantitative anti-S1 IgG ELISA was 26%, the rate was significantly lower for the Roche anti-Nucleocapsid total antibody assay (1.2%) and the Roche semiquantitative anti-RBD total antibody assay (0%).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high infectivity of the Omicron strain is most likely due to the fact that the Omicron strain infects and duplicates 70 times faster in the bronchi than the Delta strain and the original SARS-CoV-2 strain ( Dejnirattisai et al., 2022 ; Zhang et al., 2022 ). However, it is promising to note that lung infection caused by the Omicron strain is significantly less dangerous than that of the Delta strain as well as the original SARS-CoV-2 strain, which is a key indicator of the severity of the disease, and this explains to some extent the predominance of patients infected with the Omicron strain who are just ordinary patients ( Chen et al., 2022 ; Hu et al., 2022 ; Narowski et al., 2022 ). Although great efforts have been made to investigate human coronavirus disease, the molecular mechanisms of the pathogenesis of COVID-19 are still poorly studied ( Pennisi et al., 2020 ; Ritter et al., 2020 ; Yang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%